MONITORING KETIDAKSEIMBANGAN BEBAN TRANSFORMATOR DISTRIBUSI MENGGUNAKAN INTERNET OF THINGS - Zebua, Osea; Komalasari, Endah; Alam, Syaiful; Aldiansyah, Aldiansyah (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2021)
Unbalanced load is one of the causes of unpredictable distribution transformer failure, so it is necessary to monitor the unbalanced load condition of the distribution transformer. Internet of things technology-based equipment supports remote monitoring needs. This paper presents the monitoring of unbalanced load in distribution transformer based on IoT technology. The ZMPT101B voltage sensor and SCT019 current sensor are used to measure the rms voltage and current in each phase, the Arduino microcontroller is used to process the measurement data and send it to the network server via an ethernet shield and a wifi router equipped with an internet modem. The results showed that the monitoring equipment based on IoT technology is able to work to monitor load unbalanced online so that it could be monitored remotely via device connected to the internet network